Reservoir system expansion scheduling under conflicting interests. (August 2019) - Geressu, Robel T.; Harou, Julien J.
Abstract: This work proposes a many objective approach where a schedule of new dams is optimised along-side dam selections and operating rules. We investigate the extent to which changing management rules during infrastructure system expansion increases the ability to identify best performing plans. The approach links river basin simulation to many objective robust optimisation, so that expansion plans are optimised across multiple scenarios and considering multiple metrics. The approach is demonstrated using the Blue Nile hydropower reservoir system, identifying dam activation schedules that achieve efficient trade-offs for various conflicting objectives including discounted net benefits, reliable downstream releases and energy generation. Multi-reservoir system expansion scheduling formulations with three different levels of operating rule responsiveness to expansion are compared for performance and computational requirements. Results show benefits increase when release rules change as the multi-reservoir system expands, with failure to optimally adapt operating rules loosing up to 25% of NPV. Highlights: Filling period performance may impact acceptability of new dams in large systems. Selection, operating rules, & expansion schedule of new dams optimised across many criteria. If release rules are allowed to change during system expansion, performance improves. Not updating rules during expansion loses up to 25% in financial benefits in our Blue Nile case-study. Visual analytic parallel plots can help communicate performance tradeoffs and expansion schedules.